2013
DOI: 10.1021/om301110j
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Metal and Metal–Ligand Bonds in (η5-C5H5)2M2 (M = Be, Mg, Ca, Ni, Cu, Zn)

Abstract: The metal−metal and metal−ligand bonds in a series of binuclear metallocenes (η 5 -C 5 H 5 ) 2 M 2 (M = Be, Mg, Ca, Ni, Cu, Zn) have been characterized within the framework of the atoms in molecules (AIM) theory, electron localization function (ELF), and molecular formation density difference (MFDD). The calculated results show that the metal−metal bonds in the binuclear main-group-metal metallocenes are different from those in binuclear transition-metal metallocenes. In binuclear maingroup-metal metallocenes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 47 publications
3
31
0
Order By: Relevance
“…It also gives insight into the origins of the relative bond strengths in metal-metal bonds: although both Mg-Mg and Zn-Zn bonds have strong covalent stabilization, the more easily oxidized Zn is further stabilized by ionic resonances, making it a much stronger bond. This was hinted at in a recent QTAIM study, which showed that main group-main group bonds in M2Cp 2 had more "covalent characteristics", while transition metal-transition metal bonds had "closed shell ionic characteristics" (60).…”
Section: Resultsmentioning
confidence: 90%
“…It also gives insight into the origins of the relative bond strengths in metal-metal bonds: although both Mg-Mg and Zn-Zn bonds have strong covalent stabilization, the more easily oxidized Zn is further stabilized by ionic resonances, making it a much stronger bond. This was hinted at in a recent QTAIM study, which showed that main group-main group bonds in M2Cp 2 had more "covalent characteristics", while transition metal-transition metal bonds had "closed shell ionic characteristics" (60).…”
Section: Resultsmentioning
confidence: 90%
“…Generally speaking, the electron density at the BCP reliably reflects the strength of a bond. 94 The numerical values of the ELF for all the considered molecules are listed in Table 1. A negative electron density Laplacian shows the excess potential energy at BCP introducing electronic charge concentration in the inter-nuclear region and implies a shared interaction as in covalent bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, AIM theory and ELF methods have been shown to be powerful methods to explore chemical bonding [71][72][73][74] . AIM theory uses novel descriptors, such as the electron-density distributions at the bond critical point (BCP), to provide deep insight into the 25 nature of the chemical bond.…”
Section: Topological Analysis Of Electron Densitymentioning
confidence: 99%
“…And the occurrence of NNA depends on calculated basis set and 55 method [60,84,85] ,or depends on a suitable match of radial shell and internuclear separation [71,86] .The NNA are tested by using HF, B3LYP, and M062X methods with 6-311G(d), 6-311+G(d), and 6-311G(2df), and 6-311+G(2df) basis sets. The calculated shows that the NNA are exist at all the above calculated levels.…”
Section: Aim Analysismentioning
confidence: 99%